Pengaturan Pidana terhadap Perbuatan Asusila Sesama Jenis dalam Delik Perzinaan di Indonesia - Ferdiansyah, Farhan; Usman; Erwin (AL-SULTHANIYAH, 2026)
This study aims to analyze the criminal law provisions concerning same-sex immoral acts within the context of adultery offenses in Indonesia, particularly in light of the reform of national criminal law under the 2023 Criminal Code (KUHP). The research employs a normative legal method with statutory, conceptual, comparative, and case approaches. The findings indicate that neither the old nor the new Criminal Code explicitly criminalizes sexual orientation or consensual same-sex relations between adults. The new Criminal Code instead broadens the scope of morality-related offenses through Articles 411 and 414, emphasizing the protection of morality, public order, and the institution of marriage, while restricting enforcement through the mechanism of an absolute complaint (delik aduan absolut). The legal implications demonstrate the state’s attempt to balance public morality with respect for human rights, although the potential for indirect discrimination remains in legal practice.